THE COMPREHENSION OF OVERCOMING AND NEUTRALIZING THE COUNTERACTION TO THE INVESTIGATION OF CRIMES IN CRIMINALISTICS - Verenich, Igor (Administrative and Criminal Justice, 2019)
The paper covers the issues of forming and developing theoretical concepts of overcoming and neutralizing the counteraction to the investigation of crimes.